1998
DOI: 10.1007/s004060050017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proton magnetic resonance spectroscopy of the basal ganglia in patients with affective disorders

Abstract: Proton magnetic resonance spectra were recorded from a subcortical region containing the basal ganglia in 40 patients with affective disorders (18 with bipolar disorder and 22 with major depression) and in 20 normal controls. The absolute concentration of the choline-containing compounds (Cho) in the patients with bipolar disorder in the depressive state was significantly higher than that in the normal controls. The patients with bipolar disorder had significantly higher levels of the Cho/creatine + phosphocre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 11 publications
5
76
0
6
Order By: Relevance
“…This would suggest that Cr may not be a stable resonance to be used as an internal standard or reference ratio in bipolar depression research. This certainly warrants further investigation as the current literature in bipolar disorder, although different in methodology, mood state, and brain region, has reported increased creatine (Deicken et al, 2001;Michael et al, 2003Ftrend, Hamakawa et al, 1999Fmen only), decreased creatine (Deicken et al, 2003), or no change in creatine (Hamakawa et al, 1998;Friedman et al, 2004;Cecil et al, 2002;Brambilla et al, 2005;Frey et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…This would suggest that Cr may not be a stable resonance to be used as an internal standard or reference ratio in bipolar depression research. This certainly warrants further investigation as the current literature in bipolar disorder, although different in methodology, mood state, and brain region, has reported increased creatine (Deicken et al, 2001;Michael et al, 2003Ftrend, Hamakawa et al, 1999Fmen only), decreased creatine (Deicken et al, 2003), or no change in creatine (Hamakawa et al, 1998;Friedman et al, 2004;Cecil et al, 2002;Brambilla et al, 2005;Frey et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Charles et al (12) reported that elevated choline/creatine ratios decreased after antidepressant treatment, whereas a later study by Renshaw et al (13) yielded opposite results. Hamakawa et al (14) found higher choline levels and choline/creatine ratios in bipolar patients during a depressive episode. Vythilingam et al (15) reported lower caudate Nacetylaspartate/creatine ratios and increased choline/creatine ratios in the putamen in major depression.…”
mentioning
confidence: 97%
“…In addition, increased choline/NAA ratios were also found in the basal ganglia in both the depressive and euthymic states (Hamakawa et al, 1998). As discussed above, these findings may be the expression of underlying changes in ATP expenditure and availability, oxygen consumption, and/or glutamatergic activity in BPD.…”
Section: Could Impairments Of Cellular Plasticity and Resilience Be Amentioning
confidence: 78%